Machine learning approaches to injury risk prediction in sport: a scoping review with evidence synthesis - Leckey, C.; van Dyk, N.; Doherty, C.; Lawlor, A.; Delahunt, E. (British Journal of Sports Medicine, 2025)
Objective: This study reviewed the current state of machine learning (ML) research for the prediction of sports-related injuries. It aimed to chart the various approaches used and assess their efficacy, considering factors such as data heterogeneity, model specificity and contextual factors when developing predictive models.